2020
DOI: 10.1051/e3sconf/202017505018
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical foundations of modeling the process of transport vehicles steel ropes structural defects formation

Abstract: The article presents materials on the study of mathematical modeling of splicing (binding) of steel rope used to transmit traction by friction. The developed mathematical model splicing (binding) describes the stress-strain state of strands (wires) from quasistatic loads, arising in the cyclic tension process and bending of steel rope on rope sheave, in which the resultant force in steel rope cross section is shifted relative to the central axis, causing it to bend and torsion. Using experimental data, it was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(9 citation statements)
references
References 32 publications
0
7
0
Order By: Relevance
“…Studies of the Barnaul State Agrarian University confirmed the efficiency of the FDC 6000 liquid fertilizer applicator developed by "AMAZONE" with various options for using seeders: Primera DMC, Condor and EDX in arid conditions of the Altai Territory. [24][25] In some variants of experiments, the yield and economic effect were obtained for granular fertilizers, in other variants for liquid fertilizers [5].…”
Section: Study Location Soil and Agroclimatic Characteristics In Thementioning
confidence: 99%
See 1 more Smart Citation
“…Studies of the Barnaul State Agrarian University confirmed the efficiency of the FDC 6000 liquid fertilizer applicator developed by "AMAZONE" with various options for using seeders: Primera DMC, Condor and EDX in arid conditions of the Altai Territory. [24][25] In some variants of experiments, the yield and economic effect were obtained for granular fertilizers, in other variants for liquid fertilizers [5].…”
Section: Study Location Soil and Agroclimatic Characteristics In Thementioning
confidence: 99%
“…ArgusTwin uses radars on both sides of the spreader to continuously monitor both the left and right spreader sections and, if necessary, automatically adjust the electrical spreader system independently of each other. [4][5][6] With the TS spreader, working widths of up to 54 m and at the same time an ideal border spreading pattern are possible, for this a special ISOBUS spreader -ZA-TS is used, which belongs to absolutely high-performance spreaders. Every ISOBUS machine from E3S Web of Conferences 210, 04002 (2020)…”
Section: Introductionmentioning
confidence: 99%
“…Implementation of the results of mathematical modeling leads to an improvement in traffic organization [2][3][4]. A large number of scientific articles are devoted to various concepts of traffic flow modeling [1][2][3][4][5][6]. One of the approaches is based on abstraction, when a large city with its developed road network is represented by a kind of force field.…”
Section: Information and Mathematical Approach To The Calculation Of mentioning
confidence: 99%
“…Transportation problems in metropolitan areas, such as congestion at intersections, lead to high levels of polluting emissions when a car engine is idling or running slowly. Due to the high concentration of vehicles in megalopolises, the air is depleted in oxygen and polluted by emissions from the combustion of petroleum products [1][2][3][4][5][6]. From the air, harmful products get into the water and the water environment is polluted, the ecological system is disrupted, natural and climatic conditions change.…”
Section: Introductionmentioning
confidence: 99%
“…Vibration processing provides a change in the physical and chemical properties of the surface layer of the part, as well as its activation. Given the versatility of vibration equipment, it can be used not only for coating formation processes, but also for finishing and stripping and hardening operations, which is important because reduces the cost of production [1][2][3][4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%